mTORC2 and Metabolic Reprogramming in GBM: at the Interface of Genetics and Environment - Masui, Kenta (Brain Pathol, 2015)
Metabolic reprogramming is a central hallmark of cancer, enabling tumor cells to obtain the macromolecular precursors and energy needed for rapid tumor growth. Understanding how oncogenes coordinate altered signaling with metabolic reprogramming and how cancer cells harness cellular metabolism and its metabolites for their survival may yield new insights into tumor pathogenesis. Here, we review the recently identified central regulatory role for mTORC2, a downstream effector of many cancer‐causing mutations, in metabolic reprogramming and cancer drug resistance in glioblastoma. We further consider the emerging concept that mTORC2 may connect genetics with environmental alterations in brain cancer.